Reading motivations, strategies, and interventions of teachers in bridging learning gaps - Ma. Junithesmer Rosales (Universidade Estadual de Alagoas, 2024)
The changes in the education landscape due to the pandemic allowed an agency for an understanding of a situation in elementary schools located in an urban poor area in the Philippines to strengthen literacy particularly in reading. While most studies on reading especially in the Philippines investigated on reading performance and ways to increase reading fluency of learners, it is important to investigate as well teachers' motivations, strategies, and interventions. This qualitative study described teachers' motivation, strategies and interventions to bridge learning gaps in reading. These teachers are from selected elementary schools located in the Division of San Juan City, Philippines Based on the results, teachers are motivated because they want to teach the content better and that their concern for students motivates them. Moreover, the use of various reading strategies like free reading choice, phonological activities and empathy to level with students are strengthened by interventions that are teacher, student, and community oriented.